The Effect of Work Discipline and Teamwork on Employee Performance with Organizational Citizenship Behavior as an Intervening Variable in BPJS Branch Offices in Medan Raya - Lasmaida Susy Deliana; Kiki Farida Ferine (Yayasan Multidimensi Kreatif, 2024)
This study aims to see the direct and indirect influence between the variables of work discipline, teamwork, organizational citizenship and performance. This type of research uses quantitative, this research is conducted at BPJS Employment Branch Offices throughout Medan Raya. The population of this study is 82 employees and the sample used is the entire population using a saturated sample technique. The data source used is the primary data source and data collection is carried out by distributing questionnaires. The research model used is phat analysis with smart PLS version 3.3.3. The results of this study are that Work Discipline has a positive and insignificant effect onemployee performance with the original sample value of 0.585 and P values of 0.218. Work Discipline had a negative and significant effect on Organizational Citizenship with the original sample value of -0.949 and p values of 0.000. Teamwork had a negative and insignificant effect on Employee Performance with an original sample value of -0.694 and p values of 0.304. Teamwork had a positive and significant effect on Organizational Citizenship with an original sample value of 1.720 and p values of 0.000. Organizational Citizenship had a positive and significant effect on Employee Performance with an original sample value of 1.024 and p values of 0.003. Work discipline had a negative and significant effect onemployee performance through organizationalcitizenship with the original sample result of -0.981 and p values 0.011. Team cooperation had a positive and significant effect onemployee performance through organiccitizenship with the original sample results of 1.775 and p values of 0.001.